Feasibility of rice procurement programme for poor farmers in Bangladesh - Alam, S; Haque, S; Islam, S; Jannat, A; Islam, MM (Progressive Agriculture, 2017)
The study has been conducted to examine feasibility of rice procurement system and factors influencing farmers to sell rice at procurement centers in an area of Jamalpur district. In total, 45 sampled farmers including both participant and non-participants and 15 millers who are residing in various upazillas in Jamalpur district were interviewed. Stratified sampling technique was followed to select the respondents. From the 45 farmers, 20 farmers were participating in the procurement process. To examine the financial profitability of rice procurement system, activity budget analysis was done. To find the influencing factors those encourage farmers to attend in rice procurement programme, the Logit regression model was used. The study revealed that on an average, 52 percent and 11 percent of paddy procurement targets in Boro and Aman season respectively were achieved. On the other hand, 91 percent and 49 percent of rice procurement targets in Boro and Aman season respectively were achieved. Though cost of production was higher for marginal/small farmers, but the both gross and net return was higher for medium/large farmers. Out of 9 independent variables, four variables have been found to have significant influence on adopting rice procurement system in the study area. Although, Government Boro paddy procurement has many weaknesses, but it can be reduced by taking necessary steps in making it more efficient. Progressive Agriculture 28 (2): 139-147, 2017